Sistem Informasi Pelayanan Pengaduan Masyarakat Berbasis Web Studi Kasus Polsek Sukarame - josua Armando silalahi; Arif Budiman; Adhie Thyo Priandika; Riduan Napianto (Universitas Teknokrat Indonesia, 2023)
This research was conducted on the basis of a need regarding the problem of how to create a public complaint service information system that can be accessed online at the Sukarame Police. By conducting this research, it is hoped that it can facilitate the process of serving public complaints at the Sukarame Police which can be accessed online. System development will be carried out using the Extreme Programming method. The Extreme Programming method has four stages, namely Planning (Planning) at this stage the process of collecting data, analyzing the running system, analyzing system requirements starting from Functional requirements and Non-Functional requirements. Design at this stage is the process of making UML, database design, and making a prototype of the system to be built. Coding at this stage is carried out the coding process using JavaScript and Bootstrap Framework on the front-end side and PHP and MySQL on the front-end side. back-end side. and the last one is Testing (Testing) at this stage the system testing process is carried out using black box testing. The end result of this research is a website-based public complaint system that can be accessed online either on a smartphone or computer. Based on the results of the tests that have been carried out, the public complaint system that has been created fulfills the need to be used as a medium in the process of serving public complaints at the Sukarame Police.